Variation of Fruit Color in Cakra Hijau, G1/M8 and HV-149 Chilli Pepper Cultivar: Physiology and Molecular Approach: Variation of Fruit Color in Cakra Hijau, G1/M8 and HV-149 Cultivar - Arumingtyas, Estri Laras; Zakiyah, 'Ainun Sayyidah; Monica, Rosina; Siswanto, Dian (Journal of Tropical Life Science, 2023)
The fruit color of chili pepper is an important characteristic in identification and classification and is often used as the basis for determining consumer preferences. Information on the relationship between chili fruit color and its molecular profile is very important in supporting selection activities in plant breeding. This study aims to identify genetic diversity associated with the fruit color of three genotypes of chili (Capsicum frutescens L.): Cakra Hijau, HV-149 and G1/M8, using Random Amplified Polymorphic DNA (RAPD) and Simple Sequence Repeat (SSR). Morphological confirmation was carried out according to Capsicum descriptors. Nineteen RAPD markers and six SSR markers were used for genetic variability assessment. Genetic variation was analyzed using the unweighted pair group method with the arithmetic mean and the Jaccard similarity index. The three chili genotypes had different fruit colors at each maturation stage. The immature Cakra Hijau fruit is dark green and turns dark red as it ripens. The immature fruits of the G1/M8 line are light green and turn red when ripe. Finally, immature HV-149 fruits are dark green and yellow when ripe. The SSR markers used in this study were unable to show polymorphism. On the other hand, the RAPD marker successfully detected genetic variation in the three chili genotypes and resulted in a total of 49 alleles. The average value of polymorphic information content of the RAPD primers used ranged from 0 to 0.296, with the highest index indicated by OPA-1. The dendrogram shows the separation of the three genotypes into two main clusters, with the first cluster consisting of the HV-149 variety and the second cluster consisting of Cakra Hijau and G1/M8 lines. This study revealed that there are genetic variations based on the morphological characteristics of fruit color at each ripening stage and RAPD band profile. The RAPD marker was more effective than the SSR marker for identifying the genetic diversity of fruit color in the three chilies studied.